Implementasi Mata Pelajaran Pendidikan Agama Islam Berbasis Kurikulum Terpadu di SMP Darul Hikam Integrated School Bandung - Violin Arsy Zahran Rahadian; Aep Saepudin; Fitroh Hayati (Bandung Conference Series: Islamic Education, 2022)
Abstract. Exictence of Islamic Education at school is not just about in fullfing of knowledge but it must be implemented in daily activities. Implantation of Islamic values in daily activities will not be able by Islamic teachers at school because limited time allocation. So optimization Islamic education at school must be implemented in integrated. Based on this phenomenon, the problem in this research is formulated as follows: (1) The planning of Islamic Education based on integrated curriculum ? (2)The implementation of Islamic Education based on integrated curriculum? (3) The evaluation of Islamic Education based on integrated curriculum? (4)The Supporting and obsctacle of Islamic Education based on integrated curriculum?. Researcher using correlational analysis technique using a quantitative approach. with qualitative descriptive method. This research was conducted at SMP Darul Hikam Integrated School Bandung. The data collection technique which used in this research are observation, interview and documentation. The data analysis processes are done through data collection, data reduction and conclusion.The results of this study are: The implementation of Islamic Education based on integrated curriculum at SMP Darul Hikam Integrated School is using integrated model by inserting special curriculum of Darul Hikam and integrated higher order thinking skills as implementetaion of Cambdrige international curriculum. Abstrak. Adanya mata pelajaran PAI bukan hanya sekedar dalam memenuhi aspek ilmu pengetahuan saja namun juga harus diterapkan dan ditanamkan dalam kehidupan sehari-hari. Penanaman nilai-nilai keislaman dalam kehidupan sehari-hari tidak akan dapat dilakukan oleh guru PAI semata karena alokasi waktu yang disediakan disekolah terbatas. Oleh karena itu optimalisasi Pendidikan Agama Islam mesti dilakukan secara terpadu. Tujuan penelitian ini adalah untuk mendeskripsikan (1) perencanaan mata pelajaran Pendidikan Agama Islam berbasis kurikulum terpadu, (2) pelaksanaan mata pelajaran Pendidikan Agama Islam berbasis kurikulum terpadu, (3) evaluasi mata pelajaran Pendidikan Agama Islam berbasis kurikulum terpadu serta (4) faktor penunjang dan penghambat mata pelajaran Pendidikan Agama Islam berbasis kurikulum terpadu di SMP Darul Hikam Integrated School Bandung Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif yang dilaksanakan di SMP Darul Hikam Integrated School Bandung dengan teknik pengumpulan data observasi, wawancara dan juga dokumentasi. Analisis data terdiri dari reduksi data, penyajian data dan kesimpulan. Hasil penelitian menunjukan bahwa: Impelementasi mata pelajaran Pendidikan Agama Islam di SMP Darul Hikam Integrated School menggunakan model integrated dengan menyisipkan kurikulum khas sekolah dan juga mengintegrasikan higher order thinking skills sebagai bentuk implementasi dari kurikulum internasional Cambdrige.